Gender prediction by using radio morphometric analysis of frontal sinus parameters - A prospective study with cone beam computed tomography - Bharani Krishna Takkella; Nayanala Venkata Anusha; Bhavana Sujanamulk; Tejaswini Vakamullu; Meka Purna Venkata Prabhat; Chukka RamSunil (Wolters Kluwer Medknow Publications, 2023)
Introduction: Radiology is an essential branch of medicine well known for its nature as "seeing the unseen." It is now extending its wings to the field of forensics to "identify the unseen" during mass disasters and natural calamities. Even after catastrophes, parts of the facial skeleton, such as the maxillary sinus, frontal sinus, and other alternate sections of the human facial skeleton, are being explored for sex identification. Researchers have proven that the frontal sinus is also a valuable tool for assessing the gender of a person. The frontal sinus and its structural diversity suggest that it is an important anatomical area to be analyzed for forensic purposes, notably in identifying sex using skull dimensions. Hence, this study aimed to identify sexual dimorphism by evaluating the frontal sinus using cone beam computed tomography (CBCT). Materials and Methods: In this study, a total of 50 patients were selected and were divided into two groups, group I (25 males) and group II (25 females), where the frontal sinus height (superioinferior) and width (mediolateral) dimensions were evaluated using CBCT scans All the measurements were performed in coronal sections. Results: The independent t-test and Mann-Whitney U-test were used to analyze the data. Shapiro-Wilk test was used to assess normality. Right frontal sinus height (P-0.11) and width (P-0.1), and frontal sinus index (P-0.81) were higher in males than in females. Left frontal sinus height (P < 0.001), width (P < 0.001), and frontal sinus index (P-0.64) were higher in males than in females. Left frontal sinus height and width were statistically significant, depicting the sexual dimorphism. Conclusion: The gender predictor variable of the frontal sinus in the current study using parameters such as height, width, and frontal sinus index on CBCT was higher in males compared to females. Left frontal sinus can be considered as a useful predictor in the gender determination of the individual.